Perfect Competition vs. Riskaverse Agents: Technology Portfolio Choice in Electricity Markets - Malte Sunderkötter; Daniel Ziegler (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2013)
Investments in power generation assets are risky due to high construction costs and long asset lifetimes. Technology diversification in generation portfolios represents one option to reduce long-term investment risks for risk-averse decision makers. In this article, we analyze the impact of market imperfections induced by risk-aversion on the long-term investment portfolio structure in the market. We show that risk-averse electricity market agents who receive a managerial profit share may shift the technology structure in the market significantly away from the welfare optimum. A numerical example provides estimates on the potential scale of this effect and discusses sensitivities of key parameters.
Keywords: G11; L94; Q43; C45; 330; Nodal Pricing; Market Design; Electricity Markets